Modeling Base Station Selection in Open Access Picocell Networks Using Particle Swarm Optimization - Adrian, Ronald (2015)
This paper studies the base station selection in open access picocell networks using Particle Swarm Optimization (PSO) algorithm. Mobile users can choose to connect either a picocell or a microcell to improve their signal quality. Modeling base station in an area gives various signal quality, which depends on the distance between mobile user and base station. The problem can be formulated as to select the shortest link from the mobile users to many base stations at different distances. Modification of PSO algorithm provides the selection of base stations through the calculations to find the signal power from a mobile user to a base station in term of signal to noise ratio (SNR). The simulation results show that PSO can estimate the best position of base station through the selection based on the distance and the quality of signal power. Indicator of base station selection uses the value of RMSE and coefficient of the standard error. This value determines the quality of precision, accuracy and trueness. Keywords— pso; picocell; microcell; base station